Portrait: Michael Lambek - Lambek, Michael (Religion and society, 2022)
In an article as relevant now as when it was written, asks: "How in a world of divided creeds is one to find out which is the true belief?" She draws from Gotthold Lessing's character Nathan the Wise to say (ibid.: 95): There are two possible solutions to the problem, that of the fundamentalist and that of the sage. The fundamentalist overcomes the problem of multiplicity by a return to the One. Truth can be restored only if rivals are eliminated and false pretenders unmasked. Truth and order are founded on the tyranny of the One. The solution of the sage is founded on the metaphysics of absence .... Under these conditions, multiplicity cannot be overcome. It has to be endured, tolerated. It is a permanent reminder of the fact that absolute truth is not for this world as we know it. To put it in a paradoxical way: it is the discovery of enlightenment that we are all groping in the dark.